К экологии птиц-дуплогнездников в Черноморском заповеднике - Ардамацкая, Т.Б.; Зелинская, Л.М.; Семенов, С.М. (Вестник зоологии, 1967)
Starling (Sturnus vulgaris), tree sparrow (Passer montarzus), great tit (Parus major) are the most mass species of hollow-nesting birds in the reservation. The study of the nourishment of these species showed that all of them eat the destructive insects, such as: caterpillars and pupae of Tortrix viridana L., Porthetria dispar L., Noctuidae Agrotis sp. sp. and Euxoa sp. sp., various Orthoptera, Polyphylla fullo L. etc. In nourishment of starlings' nestlings such insects amounted to 45.5% of the food, of tit-32.6% and tree sparrow — 53.9%; useful insects amounted to 6%, 14.5% and 4.4% correspondingly. After the nesting period the starlings are kept in the reservation up to the middle of June, then a part of hatches flies to the steppe, where feeds on insects and crass seeds, tree sparrows and tits feed on, mainly, on the territory of the reservation.